PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP RETENSI KARYAWAN (STUDI KASUS DI PT. SELAMAT GRUP BENGKULU) - Aji Mas, Galang; Ratnawili, Ratnawili (UM. Bengkulu, 2025)
The purpose of this study was to analyze the effect of compensation and career development on employee retention at PT. Congratulations Bengkulu Group. Several factors will be discussed in this study, including the effect of compensation and career development on employee retention. The objects in this study are employees of PT. Congratulations Bengkulu Group totaling 135 people. This research is a type of quantitative research. Data collection techniques are observation and questionnaires. Several data analysis techniques were used in this study, including data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the results of research on the effect of compensation and career development on employee retention at PT. Selamat Bengkulu Group, the following conclusions can be drawn: there is a negative and significant effect of compensation (X1) on employee retention (Y) PT. Selamat Bengkulu Group means that the higher the compensation, the employee retention will also decrease. There is a negative effect of career development (X2) on employee retention (Y) PT. Selamat Bengkulu Group means that the higher the career development, the employee retention will also decrease. There is a negative effect of compensation and career development together affecting the retention of employees of PT. Congratulations Bengkulu Group.Keywords: Compensation, Career Development, Employee Retention